IMPLEMENTASI PENDISTRIBUSIAN DANA ZAKAT INFAQ DAN SHADAQAH (ZIS) PERBANKAN SYARIAH UNTUK PEMBERDAYAAN USAHA KECIL MIKRO (UKM) DI MALANG - Yuliana, Indah (ULUL ALBAB Jurnal Studi Islam, 2010)
One of the organization models of tithe, grant, and charity fund is fund organization of qardhul hasan in syariah banking. Its model organization is giving loan toward UKM without sharing outcome. This fund derives from cutting the tithe from official and employee of syariah bank beside from bank customer. Because it is grant fund that is purposed for even distribution of economy, so its allocation must give advantage for low society. This research directs its attention to organization of ZIS from syariah banking. Kind of this research is qualitative descriptive research. The data used is obtained from field through direct observation as primary data and uses information documented forming book, journal, and scientific paper or the research result as secondary data. The organization model and ZIS of syariah bank is conducted by cooperation between BMT and mosque. The distribution of ZIS fund has consumptive and productive characteristics. For productive characteristic is distributed toward small industry micro. Giving this fund is purposed for adding extra amount of modal in order to improve industry that has been pioneered. If the industry improves, the income will increase and furthermore it is hoped that who at first is mustahiq will change to be muzakki.